The Significance of Wise Reflection (Paccavekkhana) - Aggadhamma, Aggadhamma (Journal of International Buddhist Studies, 2020)
The general conception of paccavekkhana as mindful and wise reflection, and as a key principle in Buddhist meditation practice in meditative concentration is the main concern of this undertaking. Post-Canonical literature are carefully examined for this purpose. This study has affirmed paccavekkhana as an approach to a clear understanding of reality through initial training of dasadhammā as a primary behavioral modification/refinement to meditative concentration for Buddhist soteriology. The term ‘paccavekkhana’ is characterized as the integrative intent for the sīla-samādhi-pañña framework of Buddhist praxis. The paccavekkhana practice is most crucial for spiritual practice and it is actually pragmatic advice for one’s daily living, especially the ordained. Hence, a right understanding of its value, internalization of it through a creative, and practical technique of transforming paccavekkhana into “walking the talk” via a daily checklist would give rise to a systematic and self-rectifying slant in one’s dhamma faring.